2008
DOI: 10.1021/ja800708x
|View full text |Cite
|
Sign up to set email alerts
|

Cu2+Binding Modes of Recombinant α-Synuclein − Insights from EPR Spectroscopy

Abstract: The interaction of the small (140 amino acid) protein, alpha-synuclein (alphaS), with Cu(2+) has been proposed to play a role in Parkinson's disease (PD). While some insight from truncated model complexes has been gained, the nature of the corresponding Cu(2+) binding modes in the full length protein remains comparatively less well characterized. This work examined the Cu(2+) binding of recombinant human alphaS using Electron Paramagnetic Resonance (EPR) spectroscopy. Wild type (wt) alphaS was shown to bind st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
121
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(137 citation statements)
references
References 39 publications
12
121
0
3
Order By: Relevance
“…Our data suggested that simultaneous copper binding to both the N-and C-termini simultaneous could generate oligomeric aSyn. Co-ordination of copper by a-Syn as a result of residues at distant sites has been suggested previously (46). On the basis of these results, we extended our study to the toxicity of fulllength a-Syn and its relation to copper.…”
Section: Copper and Oligomer Toxicitysupporting
confidence: 65%
See 2 more Smart Citations
“…Our data suggested that simultaneous copper binding to both the N-and C-termini simultaneous could generate oligomeric aSyn. Co-ordination of copper by a-Syn as a result of residues at distant sites has been suggested previously (46). On the basis of these results, we extended our study to the toxicity of fulllength a-Syn and its relation to copper.…”
Section: Copper and Oligomer Toxicitysupporting
confidence: 65%
“…As mentioned earlier, a-Syn binds to copper and iron (46,48,49), and a-Syn aggregation is stimulated in the presence of these metals (37,50). This has led us to examine whether the toxicity of extracellular synuclein proteins was exacerbated in the presence of metals.…”
Section: Copper and Oligomer Toxicitymentioning
confidence: 96%
See 1 more Smart Citation
“…The first coordination sphere of aSyn Early evidence from model peptides [24] and full-length aSyn140, [25,26] suggested that the protein adopted two coordination modes in the presence of 1 } (mode II). Nevertheless, numerous studies proposed only a single high affinity coordination mode, with disagreement regarding the role of Met1 and His50 and/or overlooking the effect of pH-dependent equilibrium.…”
Section: Resultsmentioning
confidence: 99%
“…This mechanism is a highly selective, site-specific process that involves interactions of the protein with both oxidation states of the copper ion. Added to the large body of evidence supporting AS-Cu(II) interactions [14][15][16][17][18][19][20], elucidation of the residue-specific basis determining the AS-Cu(I) structural-affinity features is central to establish a connection of the AS-copper interactions with the mechanistic basis-oxidative damage-behind the metal-enhanced AS amyloid assembly. In that direction, we have demonstrated recently that both Met residues in the motif 1 MDVFM 5 constitute key structural determinants for the binding of Cu(I) to the N-terminal region of AS in a Met 1 (S)-Cu(I)-(S)Met 5 coordination environment [21,22].…”
mentioning
confidence: 99%